EKSPLORASI KEJADIAN PENYAKIT BUSUK BUAH (Phytophthora palmivora) PADA TANAMAN KAKAO DI DESA CAU KECAMATAN MARGA KABUPATEN TABANAN - Yohanes Berckemas; Putu Eka Pasmidi Ariati; I Putu Sujana (Agrofarm: Jurnal Agroteknologi, 2025)
This study focuses on evaluating the extent of cocoa pod damage caused by pathogenic infections. Understanding the underlying causes of disease is essential as a foundation for making effective control decisions. Field observations revealed that pod rot is the most significant disease due to the considerable losses it causes in cocoa production. Pod rot in cocoa, caused by Phytophthora palmivora, typically begins with the appearance of small brown spots on the surface of the pod around two days after infection. These lesions rapidly expand and darken, eventually covering the entire pod. Within approximately 14 days, the pod turns completely black, and the internal tissues, including the seeds, become dry and mummified, serving as a major source of future infections. White mycelium appears on the infected surface and becomes denser as the disease progresses. This mycelium produces sporangia containing numerous spores. These spores are spread by rainwater, either through direct contact or splash dispersal, infecting other parts of the cocoa tree. The time needed for the pod to rot completely is around two weeks, depending on the pod’s size at the time of infection. Field data indicated that in Plot I, 35 pods (14.28%) and 16 trees (5.33%) were infected. In Plot II, 22 pods (16.54%) and 19 trees (9.05%) were infected, while in Plot III, 15 pods (23.07%) and 9 trees (9.89%) were affected by pod rot. Environmental factors : air humidity, rainfall, and farming practices were identified as key variables that influence the rate of disease development and spread.